Public investment and poverty: the ecuadorian case up to 2020 - Bravo Placeres, Ismael (Revista Universidad de Guayaquil, 2019)
The present article examinesthe incidence of the public investment in the Ecuador. The analysisof the problem considers the situation of the poverty in the country, an I lash from growingproportions to global scale, especially in the last years. The analysis leaves of the literatureofficially published by the Ecuadorian government and the prosecution of secondary sources.The methodology used in the work is mixed, with support in the methods characteristic of thequalitative methodology for the documental analysis of works, rehearsals and articles referredto the different focuses and theories about the public investment and the poverty. The used datathey are ofsecondary origin, because the statisticalinformation comesfrom institutionslike theNational Institute of Statistic and Census (INEC), National Secretary of Planning andDevelopment (SENPLADES), Integrated System of Knowledge and Social Statistic of theEcuador (SiCES), National Plan for the Good one to Live (PNBV), among others.
Keywords: Poverty; Public Public; Political Investment; Well-being